2021
DOI: 10.1136/openhrt-2021-001713
|View full text |Cite
|
Sign up to set email alerts
|

Using genetics to detangle the relationships between red cell distribution width and cardiovascular diseases: a unique role for body mass index

Abstract: ObjectiveRed cell distribution width (RDW) is an enigmatic biomarker associated with the presence and severity of multiple cardiovascular diseases (CVDs). It is unclear whether elevated RDW contributes to, results from, or is pleiotropically related to CVDs. We used contemporary genetic techniques to probe for evidence of aetiological associations between RDW, CVDs, and CVD risk factors.MethodsUsing an electronic health record (EHR)-based cohort, we built and deployed a genetic risk score (GRS) for RDW to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The authors suggested that relationship between RDW and cardiovascular outcomes may partly be related to aging ( 43 ). Another previous study ( 18 ) showed non-significant relationships between genetically-increased-RDW and CVDs. In accordance with the previous studies, we did not find any significant relationship between PGS-RDW and CVDs in this study with individual follow-up data.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The authors suggested that relationship between RDW and cardiovascular outcomes may partly be related to aging ( 43 ). Another previous study ( 18 ) showed non-significant relationships between genetically-increased-RDW and CVDs. In accordance with the previous studies, we did not find any significant relationship between PGS-RDW and CVDs in this study with individual follow-up data.…”
Section: Discussionmentioning
confidence: 75%
“…Several potential mechanisms were proposed to contribute to these associations, such as inflammation ( 6 ) and oxidative stress ( 7 ), which could affect red blood cell (RBC) production and erythropoiesis, and thereby RDW. There are also some previous studies of genetically predicted-RDW in relation to CVDs ( 12 , 18 , 43 , 44 ). A study from the UK Biobank reported that genetically increased RDW was not predictive for incident cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22–30 Of these, previous studies using Mendelian randomization suggest a causal effect of higher CRP on schizophrenia, though not cardiovascular disease, cancers or several other chronic diseases, and of 25(OH)D on all-cause and cancer mortality. 31–34 Furthermore, all may be accurate predictors for premature mortality and correction for random error is important whether the multivariable regression analysis is exploring causality or just association.…”
Section: Methodsmentioning
confidence: 99%
“…Anisocytosis can be assessed clinically using the metric of red blood cell distribution width (RDW), which provides information on the degree of heterogeneity or variation of erythrocyte volume and size. RDW over 14% is considered abnormal, and high RDW has been consistently associated with adverse outcomes, such as cardiovascular disease, metabolic syndrome, and mortality [2][3][4][5][6][7][8]. RDW has also been proposed as an inflammatory marker because it is associated with tumor necrosis factor-alpha and interleukin 6.…”
Section: Introductionmentioning
confidence: 99%